Microalgae as functional ingredients in savory food products: application to wheat crackers - Batista, Ana Paula (2019)
Crackers are widely consumed snack foods and there is an increasing trend in adding functional ingredients to their composition. In the present work, the dried biomasses of four microalgae strains—Arthrospira platensis F&M-C256, Chlorella vulgaris Allma, Tetraselmis suecica F&M-M33, and Phaeodactylum tricornutum F&M-M40—were used as a source of proteins, antioxidants, and other bioactive molecules in artisanal wheat crackers. Two incorporation levels were tested: 2% (w/w) and 6% (w/w). The impact of microalgae addition was evaluated in terms of physical properties, biochemical composition, antioxidant activity, in vitro digestibility, and sensory characteristics. Microalgae crackers presented stable color and texture throughout eight weeks of storage. Microalgae crackers were slightly thinner and lighter than the control but presented a similar density in agreement with scanning electron microscope images, indicating that gas retention was not greatly affected by microalgae addition. Regarding biochemical composition, 6% A. platensis and C. vulgaris crackers presented a significantly higher protein content (13.2–13.5%), for which they could be claimed to be a “source of protein” according to the Regulation (EC) No. 1924/2006. A. platensis crackers showed the highest antioxidant activity and attained better sensory analysis scores. T. suecica and P. tricornutum crackers showed high phenolic content and antioxidant activity but attained low sensory scores mainly because of their unattractive fishy off-flavor